Respuestas
Respuesta dada por:
1
f(x)=
f (
)= ![x^{2} + \frac{1}{ x^{2} } x^{2} + \frac{1}{ x^{2} }](https://tex.z-dn.net/?f=+x%5E%7B2%7D+%2B+%5Cfrac%7B1%7D%7B+x%5E%7B2%7D+%7D+)
----> f(
)(x)=
(x)
f (x+1) +(-1)= [ (
) (x)] +(-1)
f (x) =![( x^{3} + \frac{1}{x} )-1
( x^{3} + \frac{1}{x} )-1](https://tex.z-dn.net/?f=%28+x%5E%7B3%7D+%2B+%5Cfrac%7B1%7D%7Bx%7D+%29-1%0A)
Dato x mayor igual que dos, entonces
x= 2, 3, 4, 5, 6, 7.....
Podemos remplazar
f (
----> f(
f (x+1) +(-1)= [ (
f (x) =
Dato x mayor igual que dos, entonces
x= 2, 3, 4, 5, 6, 7.....
Podemos remplazar
gabymy15:
gracias!! mm pero :/ sale con algun erro de texto.. pued ser?
Preguntas similares
hace 7 años
hace 7 años
hace 7 años
hace 10 años
hace 10 años
hace 10 años
hace 10 años